Irreversible electroporation of the pig kidney with involvement of the renal pelvis: technical aspects, clinical outcome, and three-dimensional CT rendering for assessment of the treatment zone - Sommer, Christof-Matthias; Fritz, Stefan; Wachter, Miguel F.; Vollherbst, Dominik; Stampfl, Ulrike; Bellemann, Nadine; Gockner, Theresa; Mokry, Theresa; Gnutzmann, Daniel; Schmitz, Anne; Knapp, Jürgen; Longerich, Thomas; et al. (Journal of vascular and interventional radiology, 2013)
Purpose - To analyze irreversible electroporation (IRE) of the pig kidney with involvement of the renal pelvis. - Materials and Methods - IRE of renal tissue including the pelvis was performed in 10 kidneys in five pigs. Three study groups were defined: group I (two applicators with parallel configuration; n = 11), group II (three applicators with triangular configuration; n = 2), and group III (six applicators with complex configuration; n = 3). After IRE and before euthanasia, pigs underwent contrast-enhanced computed tomography (CT). Technical aspects (radial distance of applicators, resulting mean current), clinical outcome (complications, blood samples), and three-dimensional CT rendering for assessment of the treatment zone (short axis, circularity) were assessed. - Results - Radial distances of applicators were 14.3 mm ± 2.8 in group I, 12.3 mm ± 1.9 in group II, and 16.4 mm ± 3.5 in group III. Resulting mean currents were 25.7 A ± 6.5 in group I, 27.0 A ± 7.1 in group II, and 39.4 A ± 8.9 in group III. In group III, two perirenal hematomas were identified. There was no damage to the renal pelvis. During IRE, clinical blood parameters and cardiovascular markers did not change significantly. Short axis measurements were 20.6 mm ± 3.6 in group I, 31.9 mm ± 8.2 in group II, and 39.3 mm ± 2.4 in group III (P < .01 between groups). Circularity scores were 0.8 ± 0.2 in group I, 0.7 ± 0.1 in group II, and 0.7 ± 0.1 in group III, with a score of 1 indicating perfect roundness (P value not significant). - Conclusions - IRE of the pig kidney with involvement of the renal pelvis is feasible and safe. Size but not shape of the treatment zone is significantly affected by applicator configuration.
Gesehen am 09.02.2022